KARAKTERISTIK UNJUK KERJA MOTOR DIESEL INJEKSI LANGSUNG BERBAHAN BAKAR GANDA CNG-SOLAR - Prawoto, Prawoto; Sumartono, H.; Shalahuddin, L. (MESIN, 2006)
This paper describes a study that compared heat release, performance and exhaust emission from asingle cylinder direct injection engine fueled with dual-fuel (Compressed Natural Gas, CNG), with thoseIndonesian dieselfuel (solar). The dualfuel tested was mixture of about 80% CNG-20% Solar. The study isbased on the engine test bed results from Centerfor Thermodynamics, Engines and Propulsion-BPPT. Thetest results have shown that for a given engine speed, the diffusive combustion phase period on the enginefueled with dualfuel were shorter than dieselfuel, whereas the late combustion phase were longer. However,premixed orrapid combustion phase periodfor dualfuel were shorter at low speedandlonger at high speedthan thosefoundfor dieselfuel. Enginefueled with dualfuel pratically produced the same maximum torqueandpower asenginefueled with dieselfuel 100%, andean be operated on large range ofspeed. The emissiontest results have shown a lower particulate matter, slightly higher hydrocarbon (HC) andcarbon monoxide(CO) than the same enginefueled. Oxide ofNitrogen (NOx) emissionfrom dual-fueled however was generallyhigher. The data obtained in this study indicate that dualfuel has promise asan emission reducing alternativefuelfor dieselengine, mainly onparticulate emission.